Sosialisasi Kekerasan Seksual dan Bahaya Narkoba serta Pojok Pengadual Pelecehan, Kekerasan, dab Bullying di SMA Negeri 1 Pasir Penyu - Zulkarnain, Muhammad Fadly; AL-Qassya, Shadiq; Auliandra, Aisyah Nabila; Zalianti, Anisa Nadhifa; Balqis, Rahimah Ratu; Rajagukguk, Rebecca Theresia Nauli; Salsabila, Afina; Tantinaya, Fanliana; Rahman, Ridho; Maulana, Diandra Akbar; Fauza, Naila (LP2M Universitas Muhammadiyah Enrekang, 2024)
The University of Riau Kuliah Kerja Nyata Team (KUKERTA) located in Tanah Merah Village, Pasir Penyu District, Indragiri Hulu Regency, Riau Province has a work program with a literacy background. In an effort to realize literacy-based activities, the KUKERTA team is increasing awareness regarding education about sexual violence and the dangers of drugs to teenagers and students at SMA Negeri 1 Pasir Turtle. Through the Socialization of Sexual Violence and the Dangers of Drugs, the KUKERTA team succeeded in educating and increasing students' awareness. With socialization, a safe and comfortable Complaints Corner for Harassment, Violence and Bullying was created as an output of educational activities. However, there are obstacles such as concerns that the Complaints Corner will not be able to continue when the management changes. For the sake of the desired program, it is recommended that there be no coordination between BK teachers and selected PIK-R extracurricular students further and intensified so that Complaints Corner participation can continue to be maintained.